Organization And Management's View On Literature: Covid 19 - Ristiani, Ida Yunari; Rusmini, Rusmini; Suryadilaga, Muhammad Adam (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
Organization And Management is a concept that can be applied to practical aspects at this time, especially related to the pandemic and the Covid 19 outbreak. The purpose of this study is to determine previous research related to Organization and Management in 2021. The methodology used in this study is the method used in This research is a descriptive analysis using literature with literature data sourced from Scopus. The results of this study are the researchers found 1504 documents and articles of research results found documents based on the language where the dominance of the language is using English with the type of document article. The impact of these findings is that research in other languages is needed to enrich the literature.